The complete mitochondrial genome of Tachysurus virgatus (Oshima 1926) (Siluriformes: Bagridae) and its phylogenetic status - Yujie He; Jie Li (Mitochondrial DNA. Part B. Resources, 2020)
Tachysurus virgatus (Oshima 1926) is a small and benthic Bagridae species that resides in the Southern China and Viet Nam. Currently, limited published genetic information has hindered our understanding of this species. In the current study, the complete mitochondrial genome of T. virgatus was determined using next generation sequencing, which was 16,524 base pairs (bp) in length and identical to most genomes of bony fishes. Phylogenetic analyses supported four clades (I, II, III, and IV) occurring in the family Bagridae and T. virgatus formed an independent clade that was sister to the clades I and II.